2020
DOI: 10.3389/fonc.2020.01101
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Stage-Associated PBMC Biomarkers in Breast Cancer Using MS-Based Proteomics

Abstract: Background: It is well-described that the transcriptome of peripheral blood mononuclear cells (PBMCs) can be altered in the context of many malignancies to allow them avoid the effective immune response, which leads to cancer invasiveness. Here, we used an MS-based strategy to discover biomarkers in the PBMCs of breast cancer (BC) patients and validated them at different stages of BC. Methods: PBMCs were isolated from the breast cancer patients and were cultured alone or co-cultured with breast cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…For example, we found that low gene expression of ACTR2 (Figure 6B Reassuringly, most of the top-ranked targets we identified were previously proved to be involved in breast cancer progression except FAM157 [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. For example, it was reported that the actin-related protein ARP2 encoded by ACTR2 is the main component of Arp2/3 protein that promotes breast cancer proliferation and metastasis [55].…”
Section: Putative Therapeutic Targets Identified From Multi-omics Deep Learningmentioning
confidence: 71%
See 1 more Smart Citation
“…For example, we found that low gene expression of ACTR2 (Figure 6B Reassuringly, most of the top-ranked targets we identified were previously proved to be involved in breast cancer progression except FAM157 [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. For example, it was reported that the actin-related protein ARP2 encoded by ACTR2 is the main component of Arp2/3 protein that promotes breast cancer proliferation and metastasis [55].…”
Section: Putative Therapeutic Targets Identified From Multi-omics Deep Learningmentioning
confidence: 71%
“…In the somatic mutation signature layer, the top- 5H). To note, a significant portion of these topranked top signatures we identified were already found to be involved in breast cancer signaling in various biological pathways or mechanisms [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. For a comprehensive ranking of landmark omics signatures in patient classification, please refer to Supplemental Table S5.…”
Section: Ranking Of Landmark Omics Signatures Unveils Potential Therapeutic Targetsmentioning
confidence: 99%
“…Moreover, Moradpoor et al . 75 used SRSF6 to distinguish between metastatic and non-metastatic breast cancer at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs in breast cancer patients contains several immune suppressive cells, such as myeloid-derived suppressor cells (MDSCs). Interestingly, peripheral mononuclear cells (PBMCs) from patients with metastasis showed dramatic increase in SRSF6 RNA than those without metastasis ( Moradpoor et al, 2020 ). So far, little is known about the function of SRSF6 in cancer immunosuppression.…”
Section: Functions and Regulatory Mechanisms Of Serine/arginine-rich Splicing Factor 6 In Tumorigenesismentioning
confidence: 99%